Geopolitical consequences of Rusophilism of Carpathian Rusyns = Geopolityczne konsekwencje rusofilstwa Rusinów Karpackich - Mazur, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Rusophilism was an alternative for Carpathian Rusyns, including Lemkos, to Ukrainian nationalism. Russia used Interest in this ideology, for which the areas inhabited by Rusyns were geopolitically important. Positive attitude of this population could help to seize Central Europe and realize the imperial interests of Russia. The consequences are visible even today and are being used to destabilize the situation in Ukraine.
Keywords: Carpatho-Rusyns; Lemko; rusophilism; Russia; geopolitics; Rusini Karpaccy; Łemkowie; rusofilstwo; Rosja; geopolityka